How best to support individuals with IDD as they become frail: Development of a consensus statement. Issue 1 (27th June 2018) - Ouellette‐Kuntz, Hélène; Martin, Lynn; Burke, Eilish; McCallion, Philip; McCarron, Mary; McGlinchey, Eimear; Sandberg, Magnus; Schoufour, Josje; Shooshtari, Shahin; Temple, Bev
Abstract: Background: While higher rates and earlier onset of frailty have been reported among adults with intellectual and developmental disabilities (IDD), research on how best to support these individuals is lacking. Method: An international consultation relied on three consensus building methods: the Nominal Group Technique, an NIH consensus conference approach, and a Delphi survey. Results: There is agreement that person‐centered planning and aging in place should be guiding principles. Frailty must be considered earlier than in the general population with the recognition that improvement and maintenance are viable goals. Intersectoral collaboration is needed to coordinate assessments and actions. Safety and planning for the future are important planning considerations, as are the needs of caregivers. Ongoing research is needed. Conclusion: The statement offers guidance to respond to frailty among adults with IDD and fosters ongoing exchange internationally on best practice. As new evidence emerges, the statement should be revisited and revised.